La version latine et l'adaptation française de l' Historia rerum in partibus transmarinis gestarum de Guillaume de Tyr - Issa, Mireille (Brepols, 2010)
A comparison of the twelfth-century Latin chronicle of the Crusades by William of Tyre, the <span class=